On the Complexity of Implementation Some Cryptanalysis Methods by Distributed Computing - A. A. Varfolomeev; K.G. Kogos; A. M. Koreneva; V. M. Fomichev (Безопасность информационных технологий, 2011)
The subject of the research is an investigation on the distributed computing efficiency in the analysis of cryptographic systems by different key search methods: meet-in-the-middle, sequential key search and Hellman method. The leading results of the research are presented in the paper.